Implementasi Kompetensi Manajerial Kepala Sekolah Di SMP Negeri 1 Palangka Raya - Yossita Wisman; Dewi Ratna Juwita; Teresia Dessy Wardani (FKIP Universitas Palangka Raya, 2022)
The objectives of this study were: (i) to find out more about the implementation of the principal managerial competence at SMP Negeri 1 Palangkaraya: (i) planning, (ii) organizing, (iii) implementation, (iv) supervision, (v) to determine the factors supporters and inhibitors of the implementation of principal managerial competence in SMP Negeri 1 Palangkaraya. This type of research is descriptive with a qualitative approach and a type of case study. The data collection technique is done by interview, observation, and documentation study.The results showed that (i) the principal in planning was in accordance with the planning concept and strategy (ii) the principal had organized the school in accordance with the organizing function which included the arrangement of the organizational structure of the division of labor and the placement of teachers and staff according to their respective areas of expertise. -Each. (iii) the principal in carrying out the implementation function has not been implemented properly where there are three indicators that need to be improved, namely: (a) managing school / madrasah facilities and infrastructure in order to optimize utilization, this is because there are still many facilities and infrastructure has not been fulfilled and the recording of facilities and infrastructure has not been well managed, (b) managing school / madrasah and community relationships in the context of seeking support, ideas, learning resources, and school funding, (c) managing school / madrasah administration in support of achieving goals school. (vi) the principal in carrying out supervision is appropriate, namely through monitoring the planning process, and implementing learning, then conducting evaluation and follow-up. (v) Supporting factors consisting of internal factors, the ability to lead and the personality of the principal. While external factors include the support of school residents, government, supervisors, school committees and alumni, the inhibiting factors consist of internal factors, which affect the limited funds for facilities and infrastructure, lack of administrative staff, external factors are lack of parental participation, especially the problem of funds since the program began. free education.